The Analysis of Figurative Language in Album Ballads 1 by Joji - Maulana, Chardo; Sugiyartati, Arie (JEdu: Journal of English Education, 2024)
Figurative language is a way of speaking to express someones thoughts or intentions without using a literal meaning. The aims of this research are to identify types of figurative language in album Ballads 1 by Joji on Kerafs & Kennedy theory. This research used qualitative method. The source of the data in this research is the Lyric from the album Ballads 1 by Joji. They are Why Am I Still in LA, Test Drive, Rip, No Fun, Yeah Right, Come Thru, Slow Dancing in The Dark, Attention, Xnxx, Ill see you in 40, Wanted U, and Cant Get Over You. Moreover, to archive the aims of this research, the researcher used the qualitative method. The researcher uses the theory of Gorys Keraf (2009) & X.J Kennedy (1979). The result of this research shows that there are 31 data of figurative languages including simile (3), metaphor (7), hyperbole (4), personification (4), symbol (2), paradox (2), synecdoche (2), and repetition (7).